Gastrointestinal Mucormycosis following a Streptococcus pyogenes Toxic Shock Syndrome in a Previously Healthy Patient: A Case Report - Jean-François Roussy (Case Reports in Infectious Diseases, 2012)
Mucormycosis is an uncommon opportunistic infection and the gastrointestinal form is the rarest. Rhizopus sp. is the most frequent pathogen and infection occurs almost exclusively in immunocompromised patients. We describe the first case of intestinal mucormycosis occurring after a Streptococcus pyogenes toxic shock syndrome in a previously healthy patient caused by Rhizopus microsporus var. azygosporus.